A report of trials before the Right Hon. the Lord Chief Justice, and the Hon. Baron Sir Wm. C. Smith, bart., at the Special Commission, at Maryborough : commencing on the 23rd May, and ending on the 6th June - Mongan, James (British trials, 1660-1900, 1832)
Trials before the Court of the King's Bench, Ireland.